Patient satisfaction with the level of being informed about the changes in Slovenian healthcare system - Zupanc Terglav, Barbara; Selak , Špela; Vrdelja, Mitja; Kaučič, Boris; Gabrovec, Branko (Nursing in the 21st Century, 2019)
PATIENT SATISFACTION WITH THE LEVEL OF BEING INFORMED ABOUT THE CHANGES IN SLOVENIAN HEALTHCARE SYSTEMIntroduction. Patients’ satisfaction has a very important role regarding reforms of the healthcare system, which aim at improvement of health and optimisation of costs. Informed patient is one of the factors which notably influences patients’ satisfaction.Aim. To determine the level of satisfaction of Slovenian residents with the current healthcare system and how well informed they are about the draft law changes to the Healthcare and Health Insurance Act, debated in public in 2017.Methods. A descriptive, non-experimental sampling method was used (snowball method). A structured questionnaire was used as a measurement tool. The number of 488 persons finished the entire online questionnaire. The data were analysed using the SPSS programme, version 21 (significance level p